2010
DOI: 10.2147/opth.s11094
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal injection analysis at the Bascom Palmer Eye Institute: evaluation of clinical indications for the treatment and incidence rates of endophthalmitis

Abstract: ObjectiveTo report the incidence of endophthalmitis, in addition to its clinical and microbiological aspects, after intravitreal injection of vascular-targeting agents.MethodsA retrospective review of a consecutive series of 10,142 intravitreal injections of vascular targeting agents (bevacizumab, ranibizumab, triamcinolone acetonide, and preservative-free triamcinolone acetonide) between June 1, 2007 and January 31, 2010, performed by a single service (TGM) at the Bascom Palmer Eye Institute.ResultsOne case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…(patient 10 - Table 2). When we compare our rate of culture positive cases overall, 0.021%, to the rate of culture positive endophthalmitis reported in the literature of 0.009% to 0.065% 4, 5, 7 we have very similar findings. However, though cultures may yield no growth, it may not necessarily mean that the inflammation is non-infectious.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…(patient 10 - Table 2). When we compare our rate of culture positive cases overall, 0.021%, to the rate of culture positive endophthalmitis reported in the literature of 0.009% to 0.065% 4, 5, 7 we have very similar findings. However, though cultures may yield no growth, it may not necessarily mean that the inflammation is non-infectious.…”
Section: Discussionsupporting
confidence: 79%
“…4, 5, 7 In this study, there was only one case of culture positive endophthalmitis in a patient who did not receive antibiotics post-injection antibiotics. (patient 10 - Table 2).…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, we think that the differentiation between infectious and non-infectious endophthalmitis cannot be made with certainty based on clinical examination alone. Weighing the risks of not treating a case of infectious endophthalmitis with intravitreal antibiotics against the risks of injecting intravitreal antibiotics in a case of non-infectious endophthalmitis, we would recommend treating all suspected cases of endophthalmitis with intravitreal antibiotics [7,9,19,[21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we speculate that the procedure of aliquotting performed by compounding pharmacies or hospitals for bevacizumab may also increase the risk of infectious endophthalmitis. However, other reports showed that some cases of endophthalmitis resulted from intravitreal ranibizumab injections [10,11,12,18,22]. A recent publication also demonstrated no difference in the incidence of endophthalmitis after the injection of bevacizumab and ranibizumab [31].…”
Section: Discussionmentioning
confidence: 99%
“…Endophthalmitis, although a rare complication of intravitreal injection of anti-VEGF agents, reportedly occurring at an incidence rate of 0.009–0.099% per injection even after prophylactic measures have been taken [1,3,10,11,12,17,18,19,20,21,22], is a serious and major clinical concern, especially with the increase in the therapeutic use of these injections. Severe residual vision loss has been reported to occur despite prompt and appropriate management.…”
Section: Introductionmentioning
confidence: 99%